Equilibrium Analysis of Ce(III)-Indole Derivative Systems - Mohan Singh Jassal, Man; Yadav, Sushmita (Asian Journal of Chemistry, 2012)
This paper reports on equilibrium analysis of Ce(III)-indole-3-acetic acid, Ce(III)-indole-3- propionic acid, Ce(III)-indole-3-butyric acid systems at constant ionic strength (I, 0.1M KNO3) and at infinite dilution. These conditions help to maintain thermodynamic environment essentially required to equalize the values of conditional formation constant and thermodynamic formation constant. The stability and thermodynamics of the systems involved are discussed.